PERMETHRIN POTENTIAL AS AN ALTERNATIVE THERAPY FOR THE ERADICATION OF CUTANEOUS LARVA MIGRANS (CLM) - CASE REPORT - Sukmawati Tansil Tan; Yohanes Firmansyah; Hendsun Hendsun (Jurnal Kesehatan, 2023)
Creeping eruption is an infection of the skin due to active penetration and migration of nematode larvae to the epidermis of the skin. Although clinically, this disease is easy to treat; the incidence of Anthelmintik drug resistance should be considered because reports of Anthelmintik drug resistance have been around since 1957 among livestock. This case report discusses the innovative treatment for creeping eruption using 5% permethrin, commonly used for scabies and pediculosis. Reportedly, a 29-year-old woman with two serpiginous lesions in the right femoral region who was intervened with 5% permethrin cream for ten days proved effective in treating “creeping eruptions.” The patient admitted that he was very satisfied with the treatment without any side effects